Luteólise em bovinos: revisão - Trevisol, Eduardo [UNESP] (2013)
Luteolisys is known as a process were the corpus luteum (CL) regresses, initially characterized by a decrease in progesterone (P4) plasmatic concentration. Luteolisys is very complex and involves many processes triggered through the lack of maternal recognition and rise of prostaglandin F2α (PGF2α) pulsate release. Increase of pulsatility is involve with ocitocine and estrogen endometrial receptors increase. When PGF2α high concentrations bind to CL receptor a series of changes in angiogenics and vasoactivs factores gene expression are triggered influencing direct or indirectly in CL. Modifications in genetic expression are required for further increase intraluteal PGF2α concentrations and consequently decrease P4 concentrations and regressing luteal tissue. This paper objective is to review bovine luteolisys.